Computerisation of histopathology/cytology records–use of a commercial data storage system. Issue 2 (February 1984) - Subbuswamy, S G; McCormick, A; Peters, E E
Abstract : A system for computerising histopathology/cytology records using a commercial data processing system is described. It is emphasised that any system of computerising records should have some flexibility as no two laboratories have the same requirement and new applications and requirements may arise as one goes along. It is suggested on the basis of the authors' experience over the past two years that it might be worthwhile for histopathologists/cytopathologists interested in computerisation of records to consider the possibility of "user-friendly" software systems, which can be adapted to their particular requirements, rather than a tailor made system, which might be difficult to modify.